An investigation into the effects of injection behaviour on performance and emissions characteristics of a compression ignition engine fuelled with diesel and dimethyl ether - Meiring, Anton F. (My University, 2010)
The injection behaviour of diesel and dimethyl ether was investigated by means of advanced visualisation techniques and conventional performance and emissions engine testing. The results of these investigations were analysed collectively, with specific attention being paid the correlation between the injection characteristics of the two fuels, and the emissions of oxides of nitrogen. Analysis of the footage obtained clearly illustrates the differences between the injection characteristics, and analysis of the engine testing results revealed similar performance characteristics of diesel and dimethyl ether. The emissions of oxides of nitrogen are higher than those produced by diesel at low speeds, are similar at high engine speeds, and reduce with engine load. These characteristics can be attributed to the properties of the fuel and the physical geometry of the fuel injection system. Recommendations are made as to how to further this research into dimethyl ether as a viable alternative fuel.